Two Lines Enable FasTrack Breeding in Blueberry - Guo-qing Song (Journal of the American Society for Horticultural Science)
The juvenile period of blueberry seedlings typically lasts ≈3 to 4 years. To shorten this period and facilitate FasTrack breeding, we developed transgenic ‘Aurora’ blueberry plants with constitutive expression of the blueberry FLOWERING LOCUS T gene, enabling flowering of T0 transformants within just 1 year. To evaluate the potential of these transgenic lines in accelerating breeding cycles, we crossed transgenic ‘Aurora’ with transgenic southern highbush blueberry ‘Legacy’, referred to as Mu-Legacy. Mu-Legacy also exhibited early flowering mainly as a result of a transgene insertion, making it suitable for FasTrack breeding. Over 2 years of phenotyping, we observed that transgenic seedlings flowered consistently each year, whereas nontransgenic seedlings did not produce any flowers. These results suggest that either the constitutive expression of the blueberry FLOWERING LOCUS T gene or the specific transgene insertion site in transgenic ‘Legacy’ can effectively shorten the juvenile phase of blueberry plants. Given the significance of ‘Aurora’ and ‘Legacy’ in blueberry production, these transgenic lines emerge as a valuable tool for accelerating blueberry breeding programs.